MODERN WORLD OF LEARNING WITH CREATIVE SYLLABI: STRATEGIES AND OUTCOMES - Roghayeh Gavagsaz-Ghoachani (آموزش مهندسی ایران, 2025)
In the fast-paced world of modern engineering education, the need for innovative methods to capture students’ attention and enhance learning has become more critical than ever. This paper introduces creative syllabi designed to provide interactive and engaging experiences for students. Through methods like storytelling, interactive activities, and digital tools, examples of captivating syllabi are presented, and strategies for effective implementation, along with potential challenges, are explored. Insights from several years of applying these syllabi at Shahid Beheshti University in various engineering disciplines have been collected and analyzed. Student feedback has been categorized and analyzed through both qualitative and quantitative methods. The results indicate that these creative approaches can boost student engagement, deepen understanding, and foster motivation for learning. Additionally, a friendly atmosphere and reduced anxiety were also noted as benefits. This study serves as a valuable resource for instructors and curriculum designers aiming to innovate within educational processes. The creative methods proposed in these syllabi are adaptable and applicable across a range of disciplines and academic levels.